The Politics of Islamophobia in Indonesia: Reacting Religious Issues in Politics - Aryati, Ani; Suradi, Ahmad; Marpuah, Siti (UIN Sunan Gunung Djati Bandung, 2024)
This research analyses the political ramifications of Islamophobia in Indonesia, particularly how the apprehension linked to radical Islamic ideologies shapes the responses of government and political entities. Utilising a qualitative library research approach, this paper scrutinises an array of academic books, peer-reviewed journals, and scholarly articles to explore the interplay between religious anxieties and political measures. The findings indicate that the government's approach to combating perceived threats from Islamic movements involves strict enforcement of Pancasila, alleviation of fears regarding the replacement of national ideology by a caliphate, and promotion of religious moderation to deter extremism. The study highlights the politicisation of radicalism and Islamophobia, revealing the strategic use of these concerns to influence public policy and political discourse in Indonesia.